Mating system of Parashorea malaanonan (M. Blanco) Merr. (Bagtikan) in Mt. Makiling, Laguna, Philippines Creator - Gamboa-Lapitan, Portia (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2005)
Isozyme analysis of thirteen (13) families of Parashorea malaanonan (M. Blaco) Merr. from two stands in Mt. Makiling (5 in the Mudspring and 8 in the Maralas area) was undertaken to determine the mating system of the species. P. malaanonan is an ecologically and economically important species of the world-renown timber-producing family Dipterocarpaceae, which has been under heavy exploitation for the past decades. The effective conservation of the species requires, among others, information on mating system. The mating system of P. malaanonan was estimated from single-locus, ts and multilocus, tm outcrossing rate based on Ritland's mixed mating model and using Ritland's MLTR computer program version 2.4. The stand at Mudspring was more highly outcrossing (tm = 0.991) than the stand at Maralas (t m = 0.939). Biparental inbreeding was estimated to occur in 10 of the 13 families investigated. The average estimates were 0.084 for the stand at Mudspring and 0.170 for Maralas. These results indicate that P. malaanonan is a highly outcrossing species. The rate of outcrossing varied among and within the stand. Outcrossing rate was higher when flowering was in synchrony and the density of flowering trees was higher. The violation of the assumptions that a homogeneous pollen pool surrounds the mother tree and that alleles are in Hardy-Weinberg equilibrium may have caused this variation too. Information gathered from this study suggests that the most appropriate and cost-effective conservation strategy for the species is in situ conservation of P. malaanonan in the Makiling Forest Reserve. Ex situ conservation through plantation instead of seed bank establishment should also be carried out, however, to complement the in situ approach. Seeds for plantation establishment, which are recalcitrants, should be collected from as many areas and individual trees as possible.